South Central Anthem. - AMELAR, SARAH (Architectural Record, 2021)
BUILDING TYPE STUDY 1,033 MULTIFAMILY HOUSING WHEN VAUDEVILLE singer, dancer, and actress Florence Mills died in New York in 1927, at age 31, nearly 10,000 fans flocked to the funeral home to pay their respects. On that parcel, along with several adjacent ones, the nonprofit Hollywood Community Housing Corporation (HCHC) has recently completed a mixed-use, 74-unit affordable-housing complex, infused with music. The commission went to 31-year-old Los Angeles artist Myisha Arellano for two electric-hued murals that integrate Mills's likeness at billboard scale, along with quotes in her own handwriting.